Access of UK Investment Firms to the Single Market after a Hard Brexit : Third-Country Firms under the MiFID II Framework - Mäki-Hallila, Senni (fi=Turun yliopisto|en=University of Turku|, 2018)
Was the Brexit referendum of July 2016 the doomsday for UK investment firms? In the scenario of a hard Brexit, UK firms will lose their right to the so-called European passport and they will be treated as third-country firms, i.e. non-EU/EEA firms. This study examines how UK firms can access the EU Single Market in order to provide investment services and investment activities there as third-country firms under the new Markets in Financial Instruments Directive (MiFID II) and Markets in Financial Instruments Regulation (MiFIR), which entered into application on 3 January 2018. The third-country regime of MiFID II and MiFIR is split into the two legislative acts. Provision of investment services to retail clients and retail clients who have requested to be treated as professional clients (opt-up professional clients) is regulated by MiFID II, which provides an optional third-country regime based on the requirement to establish a branch. MiFIR, on the other hand, regulates access of third-country firms that wish to provide investment services or activities to professional clients and eligible counterparties. MiFIR provides an equivalence regime according to which if the host third country of the firm is deemed equivalent in effect to the MiFID II regime by the Commission, the firms of that third county can provide services throughout the Union without the establishment of branch after pursuant to a registration. In the absence of such a determination, the provision of investment services to professional clients and eligible counterparties is up to the Member States to legislate. Additionally, MiFID II and MIFIR provide an exception to the general authorisation requirement as under MiFID II and MiFiR in the form of the so-called reverse solicitation exception. This thesis concludes that the new third-country regime under MiFID II and MiFIR is patchy due to the regime not being harmonised. Furthermore, the scope of the regime is uncertain in places, creating confusion about its applicability. All in all, the third-country regimes under MiFID II and MiFIR is are a fry cry from the European passport currently enjoyed by the UK as an EU Member State.